Disrupting or reconfiguring racist narratives about Muslims? The representation of British Muslims during the Covid crisis. (February 2023) - Poole, Elizabeth; Williamson, Milly
This article examines British newspaper coverage of Muslims during the first wave of the Coronavirus crisis. A well-established trajectory of research shows that Muslims are negativized in mainstream media representation in the UK. However, it became obvious from the outset of the pandemic, that ethnic minority key workers were disproportionately affected by Coronavirus. This, alongside high levels of support for NHS staff, had the potential to challenge and shift established narratives about Muslims as questions of structural discrimination became the subject of news media discourse. This article examines whether these events were able, even momentarily, to disrupt dominant narratives about Muslims in the UK or whether the pandemic provided further opportunity for Othering discourses to be perpetuated. In the context of a tumultuous political landscape, where the politics of immigration have been linked to the politics of austerity, Muslims have been scapegoated as a threat to the nationalist project. In this context, the identifier 'Muslim' is only deemed relevant if it signifies 'difference', or to distinguish between good versus bad Muslim/immigrant. Hence, in the context of the reporting of Coronavirus, racist discourses have been reshaped as Muslim key workers are distinguished in the reporting from other Muslims. We examine how these representational practices play out through an analysis of four British newspapers (The Sun, Daily Mail, The Telegraph and The Mirror) over a months' coverage at the peak of the crisis (April, 2020).